2022
DOI: 10.3926/jotse.1191
|View full text |Cite
|
Sign up to set email alerts
|

Teacher readiness in STEM education: Voices of Indonesian Physics teachers

Abstract: STEM (science, technology, engineering, mathematics) education is widespread around the globe, with various theoretical frameworks and challenges from practical perspectives. In classroom practice, teacher readiness to conduct STEM learning is essential for its successful implementation. This study explores physics teachers’ readiness for STEM education using the Alignment, Capabilities, Engagement, or ACE, framework. Data collection is based on 101 teachers’ responses to six open-ended questions. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
16
0
2
Order By: Relevance
“…Despite this difference, it is important to highlight the high percentage of ignorance about the meaning of the STEM acronym shown by the students of the Technology specialty of the secondary education Master's degree: more than 67% did not know the meaning of STEM before participating in the seminar. These results influence the trend shown in previous research that underscores that the STEM concept is better known in educational research and not so much by future science teachers (Ortega-Torres, 2018) or that there is a "fluid perspective" according to the recent naming of Sulaeman et al (2022).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Despite this difference, it is important to highlight the high percentage of ignorance about the meaning of the STEM acronym shown by the students of the Technology specialty of the secondary education Master's degree: more than 67% did not know the meaning of STEM before participating in the seminar. These results influence the trend shown in previous research that underscores that the STEM concept is better known in educational research and not so much by future science teachers (Ortega-Torres, 2018) or that there is a "fluid perspective" according to the recent naming of Sulaeman et al (2022).…”
Section: Resultssupporting
confidence: 80%
“…Responding to the previously raised question about who should assume the leadership of STEAM education, these students, as future teachers, should be the ones who lead the inclusion of STEAM projects in the didactic plans of the corresponding levels. Their role as future teachers in the implementation of these practices is key (Sulaeman, Efwinda & Putra, 2022) and therefore requires prior analysis.…”
Section: Steam Teacher Trainingmentioning
confidence: 99%
“…Examples of experiments include electroplating, aquaponics technology, electrical installation, and others related to technology and engineering from elementary to high school levels. Although STEM implementation has been running for more than five years, only a few studies measure its success [4][5][6]. The previous study primarily used cognitive learning performance to measure the quality of its implementation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, science teachers are motivated to improve their alignment to this integration (Sulaeman et al, 2022). STEM education helps learners to have necessary learning skills through the integration of STEM disciplines.…”
Section: Stem (Science Technologymentioning
confidence: 99%
“…Previous research showed that it leads learners to meet innovations in science and technology (Sulaeman et al, 2022).…”
Section: Stem (Science Technologymentioning
confidence: 99%